Analysis of Religious Humanized Values in Madrasah Ibtidaiyah Textbooks - Agus Riyan Oktori (Doctoral Program In Elementary Madrasah Teacher Education Faculty Of Tarbiyah And Education - UIN Sunan Kalijaga Yogyakarta, 2024)
The community's wealth of good values is presented in every continuity of inter-religious life, both in educational institutions and in everyday community activities. It's just that until now, various phenomena have become increasingly widespread and this has seriously tarnished religion, especially Islam, which is known as a religion that is rahmatan lil alamin. This phenomenon can be observed by the increasing number of corruption cases in Indonesia involving government officials, cases of beatings of educators and students, sexual abuse of minors, groups of fighters acting in the name of religion, and so on. Of course, this phenomenon is enough material for reflection regarding the increasing erosion of human values in humans. Educational institutions should be able to become a locomotive to minimize problems that harm the good values taught. Therefore, this study aims to understand more deeply how the lesson texts contain religious humanist values, especially the texts of aqidah morals lessons in madrasah ibitidaiyah which contain democratic values, brotherhood values, tolerance values, and justice values. The research method used is library research using a philosophical approach. Meanwhile, the main object that will be studied in this research is the textbook on akidah akhlaq in madrasah ibitidaiyah in the 2013 curriculum by using content analysis in order to be able to find out in detail the extent to which religious humanist values are contained in the subject matter of aqeedah akhlak. The results of the research that the author found in the moral aqidah lesson text which contains features, rubrics and material descriptions are 41 features with the results of the study of 17 features containing 28 religious humanist values. In the textbook on moral beliefs, there are 225 rubrics with a total of 35 containing religious values. Finally, the material description contains 15 religious humanist values.